Shared biological pathways and processes in patients with intellectual disability: A multicenter study - SEZER, ABDULLAH (My University, 2023)
ackground Although the underlying genetic causes of intellectual disability (ID) continue to be rapidly identified, the biological pathways and processes that could be targets for a potential molecular therapy are not yet known. This study aimed to identify ID-related shared pathways and processes utilizing enrichment analyses. Method In this multicenter study, causative genes of patients with ID were used as input for Disease Ontology (DO), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes enrichment analysis. Results Genetic test results of 720 patients from 27 centers were obtained. Patients with chromosomal deletion/duplication, non-ID genes, novel genes, and results with changes in more than one gene were excluded. A total of 558 patients with 341 different causative genes were included in the study. Pathway-based enrichment analysis of the ID-related genes via ClusterProfiler revealed 18 shared pathways, with lysine degradation and nicotine addiction being the most common. The most common of the 25 overrepresented DO terms was ID. The most frequently overrepresented GO biological process, cellular component, and molecular function terms were regulation of membrane potential, ion channel complex, and voltage-gated ion channel activity/voltage-gated channel activity, respectively. Conclusion Lysine degradation, nicotine addiction, and thyroid hormone signaling pathways are well-suited to be research areas for the discovery of new targeted therapies in ID patients.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Neurology; Health Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Nöroloji (klinik); Yaşam Bilimleri; Pediatrics; Pediatrics, Perinatology and Child Health; Neurology (clinical); Life Sciences; neurodevelopmental disorder; intellectual disability; pathway analysis; enrichment analysis; KEGG; ontology; ASSOCIATION; METABOLISM; CHANNELS; INSIGHTS; GENETICS; GENES; TOOL; urodevelopmental disorder; intellectual disability; pathway analysis; enrichment analysis; KEGG; ontolog